The Effectiveness of Social-Comparative Feedback on the Performance of Power Generation Task in Educable Mentally Retard Girls - robabeh rostami; mona rezaie; sosan jabari (Ravānshināsī-i Afrād-i Istis̠nāyī, 2015)
The goal of this study was to determine the effectiveness ofsocial-comparative feedback on the performance of power generation task ineducable intellectual disability girls. Method: The present research isan experimental study with pre-test and post-test with experimental and controlgroups. Among all elementary special schools in Shirazcity, 46 mentally retarded girl students were selected through purposefulsampling. The participants were divided into experimental and control groups(22 inthe experimental group and 24 in the control group). Results: Analysis of covariance showed that theexperimental group achieved significantly higher scores than the control group.The results of this study provide evidence for the importance of motivationalfeedback.Conclusion: Since the social-comparative feedback had a specialeffect on the performance of power generation task in mentally retardedindividuals, it is recommended that this method be used as an effectivetraining strategy in the field of special education